Resenha: CLÁUDIO, Mário. Ursamaior. Lisboa: Dom Quixote, 2000 (180 páginas). (Revista do Centro de Estudos Portugueses, 2002)
Resenha: CLÁUDIO, Mário. Ursamaior. Lisboa: Dom Quixote, 2000 (180 páginas).